An early Brunhes (<0.78 Ma) age for the Lower Paleolithic tool-bearing Kozarnika cave sediments, Bulgaria. (15th December 2017) - Muttoni, Giovanni; Sirakov, Nikolas; Guadelli, Jean-Luc; Kent, Dennis V.; Scardia, Giancarlo; Monesi, Edoardo; Zerboni, Andrea; Ferrara, Enzo
Abstract: We present a new sedimentological profile and a magnetostratigraphy of the tool-bearing Kozarnika cave sediments from Bulgaria. Modal analysis of cave infilling sedimentary texture indicates that the tool-bearing layers contain a sizable fraction of sediment interpreted as loess. We also find evidence for a relatively thick and well defined normal magnetic polarity in the upper-middle part of the section interpreted as a record of the Brunhes Chron, followed down-section by reverse polarity directions interpreted as a record of the Matuyama Chron. The lowermost levels with Lower Paleolithic tools (Layers 13a–c) lie in the early Brunhes at a nominal maximum age of ∼0.75 Ma, while the Brunhes–Matuyama boundary (0.78 Ma) falls in Layer 13 Lower immediately below. This finding represents a conspicuous revision of previous age estimates for the same tool-bearing layers.